Which of the following equations has only one solution? x 2 = 9, x(x - 1) = 9, x 2 - 6x + 9 = 0

Question

Asked 9/10/2014 11:06:01 AM

Updated 9/10/2014 11:10:03 PM

1 Answer/Comment

Flagged by yeswey [9/10/2014 11:09:01 PM]

s

Question

Asked 9/10/2014 11:06:01 AM

Updated 9/10/2014 11:10:03 PM

1 Answer/Comment

Flagged by yeswey [9/10/2014 11:09:01 PM]

Rating

8

x^2 - 6x + 9 = 0 has only one solution.

x^2 - 6x + 9 = 0

(x - 3)^2 = 0

x - 3 = 0

x = 3 which is the only solution.

x^2 - 6x + 9 = 0

(x - 3)^2 = 0

x - 3 = 0

x = 3 which is the only solution.

Added 9/10/2014 11:10:03 PM

This answer has been confirmed as correct and helpful.

Confirmed by jeifunk [9/10/2014 11:16:24 PM]

1 = 2x2 + 5x **Weegy:** (2x+3)(x?4)= 2x^2 - 8x + 3x - 12 = 2x^2 - 5x - 12 **User:** Write the quadratic equation in general form and then choose the value of "b" (2x - 1)(x + 6) = 0 **Weegy:** The quadratic equation (2x - 1)(x + 5) = 0 in general form is: 2x^2 + 9x - 5. In the form ax^2 + bx + c = 0, b = 9. (More)

Question

Updated 9/9/2014 7:49:29 AM

2 Answers/Comments

x(x2 + 1) = 0 is this quadratic **Weegy:** x= -2
(-2)2+4=0
-4+4=0
0=0 **User:** 5(4x + 2) = 3 is this quadratic **Weegy:** The equation (x + 3)(x + 4) = 5 is quadratic. **User:** (x + 3)(x + 4) = 5 is this quadratic **Weegy:** Here is a website which give you some examples
(More)

Question

Updated 9/14/2014 9:34:34 PM

3 Answers/Comments

x(x^2 + 1) = 0 This is not quadratic.

Added 9/14/2014 9:32:25 PM

This answer has been confirmed as correct and helpful.

5(4x + 2) = 3 This is not quadratic.

Added 9/14/2014 9:33:09 PM

This answer has been confirmed as correct and helpful.

(x + 3)(x + 4) = 5 This is quadratic.

(x + 3)(x + 4) = 5

x^2 + 7x + 12 - 5 = 0

x^2 + 7x + 7 = 0 which is quadratic.

(x + 3)(x + 4) = 5

x^2 + 7x + 12 - 5 = 0

x^2 + 7x + 7 = 0 which is quadratic.

Added 9/14/2014 9:34:34 PM

This answer has been confirmed as correct and helpful.

y(y + 4) - y = 6 is a quadratic equation **Weegy:** y(y + 4) - y^2 = 6 y^2 + 4y - y^2 = 0 4y = 0, y= 0 whose gragh is y axle. Thus, y(y + 4) - y^2 = 6 is a quadratic equation. This is false. (More)

Question

Updated 9/14/2014 9:27:30 PM

1 Answer/Comment

y(y + 4) - y = 6 is a quadratic equation. TRUE.

y(y + 4) - y = 6

y^2 + 4y - y = 6

y^2 + 3y - 6 = 0 which is quadratic equation.

y(y + 4) - y = 6

y^2 + 4y - y = 6

y^2 + 3y - 6 = 0 which is quadratic equation.

Added 9/14/2014 9:27:30 PM

This answer has been confirmed as correct and helpful.

Evaluate 5! + 2!. **Weegy:** What do you mean by "evaluate 5"? (More)

Question

Updated 9/12/2014 11:36:08 AM

1 Answer/Comment

5! + 2!

= (1 * 2 * 3 * 4 * 5) + (1 * 2)

= 120 + 2

= 122

= (1 * 2 * 3 * 4 * 5) + (1 * 2)

= 120 + 2

= 122

Added 9/12/2014 11:36:07 AM

This answer has been confirmed as correct and helpful.

The hypotenuse of a right triangle is 25 cm, and the shorter leg is 15 cm. Find the length of the other leg.

Question

Not Answered

Updated 9/16/2014 1:28:20 PM

1 Answer/Comment

The hypotenuse of a right triangle is 25 cm, and the shorter leg is 15 cm. The length of the other leg is 20 cm. b = sqrt [(25)^2 - (15)^2]; b = sqrt (625 - 225); b = sqrt 400; b = 20

Added 9/16/2014 1:28:20 PM

This answer has been confirmed as correct and helpful.

32,570,663

questions answered

There are no comments.